2010
DOI: 10.1603/ec09229
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and Yield Reductions From Wheat Stem Sawfly (Hymenoptera: Cephidae): Interactions With Wheat Solidness, Water Stress, and Phosphorus Deficiency

Abstract: The impact of herbivory on plants is variable and influenced by several factors. The current study examined causes of variation in the impact of larval stem mining by the wheat stem sawfly, Cephus cinctus Norton (Hymenoptera: Cephidae), on spring wheat, Triticum aestivum L. We performed greenhouse experiments over 2 yr to (1) study whether biotic (hollow versus solid stemmed host wheat) and abiotic (water, phosphorus stress) factors interact with C. cinctus stem mining to influence degree of mined stem physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 32 publications
3
32
0
3
Order By: Relevance
“…Luginbill and McNeal (1954) reported increased susceptibility to cutting in Rescue wheat when N was combined with P or P alone. Other studies report a reduction in yield and cutting damage when plants are P deficient (Delaney et al, 2010). Our N treatments generally did not affect pith expression but we did observe reduced pith in two site–years for the control and 30 kg N ha −1 N treatments (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luginbill and McNeal (1954) reported increased susceptibility to cutting in Rescue wheat when N was combined with P or P alone. Other studies report a reduction in yield and cutting damage when plants are P deficient (Delaney et al, 2010). Our N treatments generally did not affect pith expression but we did observe reduced pith in two site–years for the control and 30 kg N ha −1 N treatments (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen applied separately did not influence cutting whereas P applied alone produced a slight increase in stem cutting. In contrast, a recent Montana greenhouse study reported that P‐deficient wheat plants were most susceptible to sawfly damage (Delaney et al, 2010). In a Saskatchewan study, no effects of N or P could be detected due to the strong influence of other environmental factors (DePauw and Read, 1982), which is similar to a North Dakota study that reported significantly more sawfly cutting in fertilized plots in only one of eight experiments (O'Keeffe et al, 1960).…”
mentioning
confidence: 95%
“…The top internodes of the plant are the preferred location for sawfly oviposition (Holmes and Peterson, 1960), therefore increased pith in this area of the stem could play an important role in conferring an extra level of resistance against stem cutting or early stage larval feeding in durum wheat. The lower two internodes of the plant were previously shown to be the region where larvae feed and accumulate the bulk of their body mass before winter (Delaney et al, 2010); therefore Lillian could have a reduced level of resistance to early larval feeding in the upper internodes, but increased resistance against later stage larval feeding. Interestingly, the hollow‐stemmed check Strongfield expressed some pith at the periphery of the inner stem walls, and tended to have a thicker outer stem wall than Lillian.…”
Section: Discussionmentioning
confidence: 99%
“…T he WSS has been one of the most damaging insect pests of common and durum wheat across the northern Great Plains of North America for more than a century (Beres et al, 2011c). Severe yield losses occur when WSS larval feeding activity damages the inner stem tissue, which reduces flag leaf photosynthetic ability (Delaney et al, 2010), and damages vascular bundles impairing the flow of water and nutrients to the developing grain (Morrill et al, 1992). The greatest sawfly damage occurs in the southern parts of Alberta and Saskatchewan, southeastern Manitoba, and throughout Montana, North Dakota, South Dakota, and western Minnesota (Beres et al, 2011c).…”
mentioning
confidence: 99%
“…Females usually lay one egg within a wheat stem per visit, reportedly in the uppermost developing internode (Holmes & Peterson, 1960), but there can be multiple eggs deposited in a stem by different females . Larvae feed internally on the parenchyma and vascular tissue, damaging the stem and reducing kernel weight by up to 35% (Holmes, 1977;Delaney et al, 2010). As the wheat plant matures, the larva moves down to the base of the stem where it cuts a notch at ground level, causing the plant to fall over before harvest and creating further yield loss (Beres et al, 2007).…”
Section: Introductionmentioning
confidence: 99%